Bootstrapping Nonparametric Prediction Intervals for Conditional Value-at-Risk with Heteroscedasticity - Emmanuel Torsen; Lema Logamou Seknewna (Journal of Probability and Statistics)
Using bootstrap method, we have constructed nonparametric prediction intervals for Conditional Value-at-Risk for returns that admit a heteroscedastic location-scale model where the location and scale functions are smooth, and the function of the error term is unknown and is assumed to be uncorrelated to the independent variable. The prediction interval performs well for large sample sizes and is relatively small, which is consistent with what is obtainable in the literature.